DAMPAK PELANGGARAN BATAS MAKSIMUM PEMBERIAN KREDIT TERHADAP NASABAH PENYIMPAN DANA - Elita Tia Monica Manalu; Renova Simanullang; Enjelia Nova Sari Simarmata; Neibi Ezenia Ambarita; Hamonangan Siallagan (Jurnal Akuntansi Kompetif, 2026)
The "Impact of Violating the Maximum Credit Limit on Depositors" discusses the important role of banks as financial intermediaries that collect and distribute public funds. Banks are required to apply the principle of prudence to maintain their health and stability, especially in providing credit based on the trust that debtors can repay loans as agreed. Providing credit that exceeds the maximum credit limit (BMPK) risks causing bad debts, damaging customer trust, and reducing bank health. This study uses a literature study to analyze the regulation of the BMPK as a supervisory instrument so that bank funds are not concentrated in certain groups and the impact of violations on depositors. Violations of the BMPK can result in sanctions for banks and the risk of loss for customers. Therefore, it is important to enforce the BMPK strictly to protect customers while maintaining the stability of the national banking system. This study shows the need for strict supervision and accountability of banking institutions in providing credit. Keywords: Maximum Credit Limit (BMPK), Bank Health, Sanctions,Customer Protection, Bank Supervision